Qualities of Single Electrode Stimulation as a Function of Rate and Place of Stimulation with a Cochlear Implant. Issue 3 (May 2016) - Landsberger, David M.; Vermeire, Katrien; Claes, Annes; Van Rompaey, Vincent; Van de Heyning, Paul
Abstract : Objectives: Although it has been shown previously that changes in temporal coding produce changes in pitch in all cochlear regions, research has suggested that temporal coding might be best encoded in relatively apical locations. The authors hypothesized that although temporal coding may provide useable information at any cochlear location, low rates of stimulation might provide better sound quality in apical regions that are more likely to encode temporal information in the normal ear. In the present study, sound qualities of single electrode pulse trains were scaled to provide insight into the combined effects of cochlear location and stimulation rate on sound quality. Design: Ten long-term users of MED-EL cochlear implants with 31-mm electrode arrays (Standard or FLEX SOFT ) were asked to scale the sound quality of single electrode pulse trains in terms of how "Clean, " "Noisy, " "High, " and "Annoying" they sounded. Pulse trains were presented on most electrodes between 1 and 12 representing the entire range of the long electrode array at stimulation rates of 100, 150, 200, 400, or 1500 pulses per second. Results: Although high rates of stimulation are scaled as having a Clean sound quality across the entire array, only the most apical electrodes (typically 1 through 3) were considered Clean at low rates. Low rates on electrodes 6 through 12 were not rated as Clean, whereas the low-rate quality of electrodes 4 and 5 were typically in between. Scaling of Noisy responses provided an approximately inverse pattern as Clean responses. High responses show the trade-off between rate and place of stimulation on pitch. Because High responses did not correlate with Clean responses, subjects were not rating sound quality based on pitch. Conclusions: If explicit temporal coding is to be provided in a cochlear implant, it is likely to sound better when provided apically. In addition, the finding that low rates sound clean only at apical places of stimulation is consistent with previous findings that a change in rate of stimulation corresponds to an equivalent change in perceived pitch at apical locations. Collectively, the data strongly suggest that temporal coding with a cochlear implant is optimally provided by electrodes placed well into the second cochlear turn. Abstract : This study investigated the effects of stimulation rate and cochlear location on sound quality of single electrode pulse trains with cochlear implant users with 31 mm electrode arrays. Previous work demonstrated temporal coding can be provided at any cochlear location. Nevertheless, low rates of stimulation which are used to encode temporal information may have a better sound quality at deeper cochlear locations which naturally process lower frequencies. Results show that sound quality is good at high rates across the entire cochlea, but low rates sound better at apical locations, suggesting a potential benefit of temporal coding on apical electrodes.